2018
DOI: 10.3390/separations5030039
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Solvents and Extraction Methods on Recovery of Bioactive Compounds from Defatted Gac (Momordica cochinchinensis Spreng.) Seeds

Abstract: Gac (Momordica cochinchinensis Spreng.) seeds contain bioactive compounds with medicinal properties. This study aimed to determine a suitable solvent and extraction technique for recovery of important compounds, namely, trypsin inhibitors, saponins, and phenolics. The antioxidant capacity and total solids of derived extracts were also measured. Water with conventional extraction method gave the highest value of trypsin inhibitor activity (118.45 ± 4.90 mg trypsin g −1 ) while water-saturated n-butanol and meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 44 publications
(60 reference statements)
0
5
0
Order By: Relevance
“…During extraction, the dissolution of phytochemicals varies according to the type of solvent used. In the other studies, it has been determined that although solvents are recommended for the extraction of phenolic compounds and saponins, water can dissolve non-phenolic antimicrobial substances and also the best option for the extraction of trypsin inhibitors [30]. Besides, water extraction could be preferred due to the safety and environmental concerns.…”
Section: Resultsmentioning
confidence: 99%
“…During extraction, the dissolution of phytochemicals varies according to the type of solvent used. In the other studies, it has been determined that although solvents are recommended for the extraction of phenolic compounds and saponins, water can dissolve non-phenolic antimicrobial substances and also the best option for the extraction of trypsin inhibitors [30]. Besides, water extraction could be preferred due to the safety and environmental concerns.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, ethanol was used as an extraction solvent due to its safety and good extraction activity to obtain the desired antimicrobial components from the plant materials [77]. 4.0 g dried powder of each TCMP was extracted two times with 40 mL of 80% (v/v) ethanol using an ultrasound-assisted extraction method (1 h, 40 • C, and 480 W) to improve extraction efficiency and the yield of antibacterial compounds in the plants [55,78,79]. Each extract was centrifuged at room temperature (900× g, 15 min), and the supernatants were collected, combined, and concentrated using a rotary evaporator (RE-52AA, Shanghai Ya Rong Co., Ltd, Shanghai, China) at 40 • C under vacuum.…”
Section: Preparation Of Plant Extractsmentioning
confidence: 99%
“…The TIA was calculated in terms of milligrams of pure trypsin inhibited per gram on a dry-weight basis (mg/g DW) of the defatted Gac seed kernel powder or the FD-TIP (Equation ( 2)) [14].…”
Section: • Calculationsmentioning
confidence: 99%
“…In one study [13], a mixture of acetonitrile, water and formic acid (ACN/Water/FA) was found to be optimal for extracting cysteine knot peptides from Gac seeds, some of which are trypsin inhibitors. In our previous study [14], we showed that trypsin inhibitors were able to be effectively extracted from defatted Gac seed kernel powder using conventional solvent extraction with deionised (DI) water only. For other plant sources of TIs, water was also the optimal solvent for their extraction from Thai mung beans [15] but 0.1M NaCl was the best for their extraction from Chenopodium quinoa seeds [16] and 0.02 M NaOH was the best for their extraction from grass peas [17].…”
Section: Introductionmentioning
confidence: 99%